Thriving in the new economy : lessons from today's top business minds - LaRocco, Lori Ann, 1971- (Wiley, 2010)
This book gives you a unique look at what some of today's best economic and business minds are doing to stay ahead of the pack. Filled with profiles of top industry leaders, it offers inspirational personal stories, useful advice, and actionable strategies you can use to skirt financial peril, seize opportunities, and flourish tin today's economy.